2010
DOI: 10.1590/s0102-76382010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Influência da atividade física no tempo livre em pacientes no seguimento de até dois anos após CRM

Abstract: Influência da atividade física no tempo livre em pacientes no seguimento de até dois anos após CRMInfluence of physical activity during leisure time in patients in the two-year follow-up period after CABG 360MARTINI, MR ET AL -Influence of physical activity during leisure time in patients in the two-year follow-up period after CABG Rev Bras Cir Cardiovasc 2010; 25(3): 359-364 b) Development of pathologic Q waves; c) Coronary intervention (e.g. percutaneous transluminal coronary angioplasty);When patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
0
13
0
10
Order By: Relevance
“…An overview of the included studies can be viewed in table 1 . In the studies by Markou et al , 12 14 Nery et al 13 16 and Martini et al , 15 they evaluated CABG-only patients. Rengo et al , 17 Giaccardi et al , 18 Cacciatore et al , 19 Noyez et al 20 and Min et al 21 evaluated both CABG and/or valve procedures, and van Laar et al 22 evaluated isolated aortic valve repair patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the included studies can be viewed in table 1 . In the studies by Markou et al , 12 14 Nery et al 13 16 and Martini et al , 15 they evaluated CABG-only patients. Rengo et al , 17 Giaccardi et al , 18 Cacciatore et al , 19 Noyez et al 20 and Min et al 21 evaluated both CABG and/or valve procedures, and van Laar et al 22 evaluated isolated aortic valve repair patients.…”
Section: Resultsmentioning
confidence: 99%
“…Rengo et al , 17 Giaccardi et al , 18 Cacciatore et al , 19 Noyez et al 20 and Min et al 21 evaluated both CABG and/or valve procedures, and van Laar et al 22 evaluated isolated aortic valve repair patients. The average age of participants in different studies ranged from 60 years (Martini and Nery et al 15 16 ) to 75 years (Rengo et al , Giaccardi et al , Min et al , van Laar et al 17 18 21 22 ). Rengo et al , 17 Giaccardi et al , 18 Min et al 21 and van Laar et al 22 excluded patients with physical impairments or with New York Heart Association heart failure class IV symptoms (severe cardiac symptoms), but in general exclusion criteria were not explicitly reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In this observational cohort study, patients were classified as being active (those involved in physical activity at least three times a week and 20 minutes or more in the last 2 weeks) and sedentary (anything less than active) according to LTPA. Patients also were given the Baecke Questionnaire of Habitual Physical Activity to confirm active versus sedentary physical activity status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the RPE scale appears to have a correlation with some hemodynamic variables and thus may be a useful tool for this group of patients. Martini and Barbisan7 investigated the effect of physical activity in leisure time on the prognosis of patients two years after coronary artery bypass grafting and found that such activity does not modify the late prognosis but that the bypass graft itself promotes physical activity and improves long-term functional capacity.…”
Section: Introductionmentioning
confidence: 99%